Beyond Kafala: Employer roles in growing vulnerabilities of women migrant domestic workers - Abdulrahim, Sawsan; Cherri, Zeinab; Adra, May; Hassan, Fahed (Centre of Excellence for Development Impact and Learning, 2023)
Women migrant domestic workers (WMDWs) constitute 7.7 percent of migrant workers worldwide, of whom more than a quarter live and work in the Arab region. In Lebanon, as in other Arab countries, WMDWs are recruited through the sponsorship system, Kafala. Under this system, a potential migrant worker can only obtain legal residency and a work permit in the country of destination if she is sponsored by a specific employer. Once in the destination country, the worker cannot transfer to a new employer unless granted permission by the original sponsor. The system heightens the social, economic, and legal vulnerability of WMDWs and has been described as unfree or bound labor and a system of racialized servitude. Yet, Kafala is not a written policy but rather a collection of administrative procedures, customary practices, and socially acceptable norms that are maintained by various players throughout the migration process. The question then arises as to whether advocacy efforts that focus on abolishing Kafala as a legal term would mitigate employers’ exploitative practices that violate the workers’ rights and freedoms, particularly in a country like Lebanon. This policy brief is based on a study carried out under the International Labour Organization’s (ILO) Work in Freedom project designed to mitigate the exploitation and forced labor of women migrating from South to West Asia to work in the domestic and garment sectors. This brief explores knowledge, awareness and attitudes to Kafala by employers in Lebanon.